Prevalence of metabolic syndrome among hypertensive subjects in abuja, Nigeria (2012)
Background: It is well known that factors like high blood pressure, hyperglycemia, dyslipidemia, obesity and hyperuricemia tend to cluster together giving rise to what is called metabolic syndrome. In spite of the high prevalence of hypertension in Nigeria, there is a dearth of data describing the prevalence of metabolic syndrome in Nigerian hypertensive patients. We therefore set out to look at the prevalence of metabolic syndrome in hypertensive patients presenting to the cardiology clinic of a tertiary institution in Abuja, Nigeria. Methods: Metabolic syndrome was defined in patients according to the World Health Organisation’s definition. Results: Of the 362 patients studied, 56.9% were male and 43.1% were female. The mean age was 51.80 6 11.63 years, mean duration of hypertension was 8.90 6 3.95 years, mean body mass index was 29.36 6 6.12 kg/m2 and mean arterial blood pressure was 110.28 6 18.17 mm Hg. Overall, 13.0% of the study population had metabolic syndrome; 16.7% of females and 10.2% of males. Conclusion: The prevalence of metabolic syndrome among hypertensive patients in Abuja, Nigeria is comparable to rates observed in some general populations in Europe. This might imply the epidemiological transition in disease pattern already being experienced in many parts of sub-Saharan Africa.